Photoinduced direct hydration of dipyridylacetylenes in acidic aqueous solution. Issue 55 (10th June 2020) - Li, Ya; Su, Zimu; Hao, Haijun; Zhuang, Junpeng
Abstract : The straightforward and catalyst-free photoinduced hydration reaction of dipyridylacetylenes in acidic aqueous solution was achieved upon UV irradiation at room temperature. Abstract : Photoinduced direct hydration of dipyridylacetylenes (DPAs) in acidic aqueous solution was achieved upon UV irradiation at room temperature. This is a catalyst-free reaction with moderate-to-good yields, and asymmetric dipyridylacetylenes afford the corresponding Markovnikov addition products.